Design of Co1Al3(OH)m/carbon nitride hybrid nanostructures for enhanced capacitive energy storage in an alkaline electrolyte. Issue 23 (5th October 2021) - Panda, Prajnashree; Mishra, Ranjit; Panigrahy, Sonali; Barman, Sudip
Abstract : Layered double hydroxide (LDH) nanostructures have attracted the attention of the scientific community owing to their facile synthesis, interesting structure and morphology, and have been promising in the field of energy storage applications. Abstract : Over the past few years, layered double hydroxide (LDH) nanostructures have attracted the attention of the scientific community owing to their facile synthesis, interesting structure and morphology, and have been promising in the field of energy storage applications. In this work, we have synthesized CoAl LDH over a graphitic carbon nitride (CN x ) surface by varying the ratio of Co : Al and among them, the Co1 Al3 (OH) m /CN x composite was found to have the maximum electrochemical behaviour for supercapacitor application in alkaline electrolytes. Interestingly, it exhibits a 3D nano flower-like structure which provides a high specific capacitance ( C s ) value of 138 mA h g −1 (1000 F g −1 ) at 1 A g −1 current density and cyclic durability of approximately 84.46% after 4500 cycles at 10 A g −1 current density. In addition, we obtained a specific capacitance of 71.5 F g −1 at 1 A g −1 current density along with long-term cyclic stability for the asymmetric supercapacitor (ASC) Co1 Al3 (OH) m /CN x //AC assembled with Co1 Al3 (OH) m /CN x and activated carbon (AC) as the positive and negative electrodes respectively. Furthermore, an energy density of 22.35 W h kg −1 is obtained at 750.2 W kg −1 power density in ASC. The enhanced charge storage property of the aforementioned material can be attributed to the high surface area of the composite and the synergetic interaction between CN x and CoAl-LDH. Moreover, this facile synthesis method is promising for designing a novel and cost-effective electrode material for supercapacitor applications.